Forecasting Model: The Case of the Pharmaceutical Retail - Burinskiene, Aurelija (Frontiers in Medicine, 2022)
Many forecasting methods are used to predict sales, such as the moving average method, naive method, exponential smoothing methods, Holt’s linear method, and others. The results brought by these models are quite different. Forecast delivered by the naive method is entirely accurate for an extended period, like 3-5 years, Holt’s methods are bringing accurate one-year period forecasts. Planning decisions have several levels, meaning different forecasting results. However, the authors that are testing various forecasting methods are not discussing results researched in different planning levels. The study is given to the construction of the forecasting model covering both planning levels, which later is empirically tested for Lithuania retail case: Purpose – the development of forecasting model for reduction of shortages in prescribed drug supply. To achieve this goal, the author revises the improvement of drug availability weekly. Research methodology – the construction of the forecasting model is incorporating outliers’ detection method and sales by pharmacies to minimise shortage. In the forecasting model, the author uses Theil’s U2 test to evaluate forecasting accuracy. Findings – During analysis, the author constructs the model which application for forecasting drugs sales where weekly availability is highly recommended. The results show that forecasting on individual pharmacies level using the integration of these plans approach leads to higher accuracy.. Research limitations – the research covers three months of sales data. For the future, the study could review other periods. In the future, the study could review other periods. The author has incorporated the review of eight forecasting methods into the study by leaving other forecasting methods unresearched. Practical implications – presented forecasting model could be useful for practitioners, which analyse the reduction of the shortage of prescribed drugs. There the revision of repeated purchases is recommended for national authorities, wholesalers and pharmacies aiming to minimise shortage. Originality/Value – the analysis to reach the highest forecast accuracy and identification of forecasting approach which respond to the fluctuation of weekly sales for the whole pharmacy chain and separate pharmacies. The study contributes to drugs’ sales review, where most authors analyse total volume, which is not separated by pharmacies.